Neocybernetics and Narrative - Clarke, Bruce (Book collections on Project MUSE., 2014)
Neocybernetics and Narrative opens a new chapter in Bruce Clarke's project of rethinking narrative and media through systems theory. Reconceiving interrelations among subjects, media, significations, and the social, this study demonstrates second-order systems theory's potential to provide fresh insights into the familiar topics of media studies and narrative theory. A pioneer of systems narratology, Clarke offers readers a synthesis of the neocybernetic theories of cognition formulated by biologists Humberto Maturana and Francisco Varela, incubated by cyberneticist Heinz von Foerster, and cu.